Pemodelan Banjir Rob Wilayah Jakarta Utara Menggunakan Sistem Informasi Geografis - Indah Ferdiani Zuhriah; Bambang Setiadi; Seftiawan Samsu Rijal (Jambura Geoscience Review, 2022)
Rising sea levels originating from high tides and inundating land are known as tidal flooding. The cases of tidal floods are increasing day by day, especially in areas directly adjacent to the high seas. One of the areas that are prone to tidal flooding is North Jakarta. This study aims to determine the areas affected by the tidal flood and the extent of the area affected by the tidal flood in the Jakarta City area. This research can be used to take preventive action for residents to face the tidal flood disaster. The tidal flood height modeling was obtained based on the value of Mean Sea Level (MSL), Higher High Water Level (HHWL), and the trend of global rising tides. The result of this study is a map of areas affected by tidal flooding, where the lowest is at an altitude of 0.4 m in Penjaringan and Cilincing. At the height of this tidal flood, the impact was approximately 54 hectares of residential areas, 59 hectares of buildings, and 146 hectares of agricultural activities. The highest area affected by the tidal flood is at an altitude of 1.96 m which inundates the coastal District of Penjaringan, Cilincing, Pademangan, and Tanjung Priok Port. The height of the highest tidal flood impacts 983 ha of residential areas, 493 ha of buildings, and 830 ha of the agricultural sector were inundated. At the height of the tidal flood, which is almost 2 m high, it is necessary to carry out careful disaster mitigation efforts for the local government.